IMPLEMENTASI MODEL GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) DALAM PEMBELAJARAN HUKUM NEWTON DI SMA - Nanda Nurarivikka Fauzi; Indrawati Indrawati; Albertus Djoko Lesmono (JURNAL PEMBELAJARAN FISIKA, 2017)
This article resulted of research "The Influence Model of GI-GI Against Learning Achievement of Physics and Students Scientific Attitude in Learning The Newton Laws in SMA". The purpose of this study was to examine the influence of model GI-GI against the results of the cognitive learning of physics, and scientific attitude of students on the material law of Newton in SMA Negeri Candipuro. This research was kind of research experiments using the design of the post test only control group. The population was class X SMA Negeri Candipuro in this research. The research sample was class X-1 as experimental class and class X-2 as the class of the control. Cognitive learning results students data were obtain through post-test and analyzed using independent sample t-test with the help of SPSS 22 research to test the hypothesis. Student attitude data obtained via the question form and analyzed using independent sample t-test with the help of SPSS 22 research to test the hypothesis. The results of the analysis of the independent sample t-test against cognitive learning results students showed the value of Sig. 0.000 < 0.05, then H0 is rejected. The results of the analysis of the independent sample t-test a scientific attitude towards students showed the value of Sig. 0.011 < 0.05, then H0 is rejected. Based on the analysis results can conclusioned the learning model GI-GI influence on the results of a study of cognitive and scientific attitude of students in learning the law of Newton in SMA Negeri Candipuro. Key words : GI-GI model, student’s cognitive learning achievement, student’s scientific attitude